Anesthetic Management in Obstructive Sleep Apnea: A Narrative Review - Surma, Alicja; Agnieszka Parafianowicz (Journal of Education, Health and Sport, 2024)
Obstructive Sleep Apnea (OSA) introduces substantial difficulties in the management of anesthesia, largely due to its implications for airway management, sensitivity to sedative agents, and an elevated risk of complications during the perioperative period. This narrative review seeks to offer an in-depth exploration of the contemporary approaches to anesthesia management in patients diagnosed with OSA. It covers the entire continuum of care, including preoperative, intraoperative, and postoperative phases. The review underscores the critical importance of an accurate and thorough diagnosis of OSA, which is essential for formulating effective anesthetic strategies. Risk stratification is emphasized as a key element in identifying the specific challenges posed by each patient’s condition and tailoring the anesthesia plan accordingly. By examining current practices and recommendations, the review aims to provide insights into how individualized anesthetic plans can be designed to reduce the risk of perioperative complications and enhance patient safety